2012
DOI: 10.1017/s0266462312000104
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pharmaceutical Reimbursement Agencies' Processes and Methods in France and Scotland

Abstract: Objectives:Pharmaceutical reimbursement agencies’ processes and methods of appraisal vary across countries. The objective of this study was to examine the contribution of formal health economic analysis in a process using such analysis in Scotland in comparison to a process not routinely using such analysis in France.Methods:A framework for classifying reimbursement systems was used to analyze the two systems. A typology of recommendation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The comparisons of eight European HTA agencies in this study, build on previous research by Nicod and Kanavos (2012) and Bending et al (2012). Nicod and Kanavos evaluated HTA recommendations from Australia, Canada, England, Scotland, and Sweden with a particular focus on therapeutic areas and identified significant variation between national recommendations.…”
Section: Discussionmentioning
confidence: 87%
“…The comparisons of eight European HTA agencies in this study, build on previous research by Nicod and Kanavos (2012) and Bending et al (2012). Nicod and Kanavos evaluated HTA recommendations from Australia, Canada, England, Scotland, and Sweden with a particular focus on therapeutic areas and identified significant variation between national recommendations.…”
Section: Discussionmentioning
confidence: 87%
“…HTA methodologies have been implemented in many ways across OECD countries. Studies of HTA processes and outcomes have revealed differences in the way costs and benefits are accounted for in the assessments [9], differences in the scope and timeliness of appraisals [10] and the contextual factors impacting the role of HTA in http://dx.doi.org/10.1016/j.healthpol.2014.12.013 0168-8510/© 2015 Elsevier Ireland Ltd. All rights reserved. The drug must: (1) be safe and efficacious, (2) have a well-defined indication, (3) have a price which is reasonable given the therapeutic value.…”
Section: Introductionmentioning
confidence: 99%
“…One study has shown that all substances evaluated by HAS between 2005 and 2010 have entered subsequent price negotiations. 33 In countries that base their decisions on cost-effectiveness information, such as the UK 34 and Australia, 35 coverage decisions are frequently made for specific patient subgroups, particularly those that show favorable cost-effectiveness. Although IQWiG and the FJC evaluate patient subgroup sizes, we did not find any significant associations between patient subgroup size and the rating decisions made by the FJC at patient subgroup level.…”
Section: Discussionmentioning
confidence: 99%